Applied of Balanced Scorecard (BSC) Approach with Determination and Weighting of Key Performance Indicator (KPI) for Employee Performance Measurement - Muhammad Nushron Ali Mukhtar; Agung Setiawan; Djoko Adi Walujo (Tibuana, 2021)
The many types of production of goods in a company spearhead the progress of this company in industrial competition in Indonesia, the variety of types of products and large production capacity makes this company need a large number of employees to balance the variety and production capacity. This large number of employees creates its own problems, one of the problems is employee performance appraisal, employee performance appraisal in this company is only centered on the highest supervisor's consideration in one section. From that problem, the researcher wants to solve the problem using the Balanced Score Card (BSC) method by using the determination and weighting of Key Performance Indicators (KPI). The final result of the research conducted at PT Alam Jaya Primanusa in May 2018 the results of the following employee achievement grades and categories: Average material value: 76.65 Fair category, Operator's average value: 85.51 Good category, Average value - Selector section average: 89.79 Good category, Packer section average value: 94.98 Good category, Values ​​in each of these sections become the basis for calculations for all injection division production, so conclusions are drawn for the final value and achievement category of all injection division production the value of 83.37 in the Fair category.